Detection of Intratumor Heterogeneity in Modern Pathology: A Multisite Tumor Sampling Perspective - Cortés, Jesús M.; de Petris, Giovanni; López, José I. (Frontiers in Medicine, 2017)
Current sampling protocols of neoplasms along the digestive tract and in the urinary bladder have to be updated, as they do not respond to the necessities of modern personalized medicine. We show here that an adapted version of Multi-site Tumor Sampling (MSTS) is a sustainable model to overcome current deficiencies in digestive and bladder tumors when they are large enough so as to make unaffordable a total sampling. The new method is based in the divide-and-conquer algorithm and includes a slight modification of the MSTS, proved to be useful very recently in clear cell renal cell carcinoma. This in silico analysis confirms the usefulness of MSTS for detecting intratumor heterogeneity (ITH) in tumors arising in hollow viscera. However, MSTS does not seem to improve routine traditional sampling in detecting tumor budding, extramural venous invasion and perineurial invasion. We conclude that 1) MSTS is the best method for tumor sampling to detect ITH balancing high performance and sustainable cost, 2) MSTS must be adapted to tumor shape and tumor location for an optimal performance.